Preparation method and application of aroma-releasing melamine-modified urea-formaldehyde resin with low free formaldehyde content
By using fragrance-release micro-free formaldehyde content melamine-modified urea formaldehyde resin and Chinese herbal powder in fiberboard production, the odor problem of fiberboard is solved, and the goal of reducing formaldehyde release, improving bonding strength and antibacterial effect is achieved, enhancing the market competitiveness of the product and human health and safety.
Patent Information
- Application Number
- CN202411925906.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The formaldehyde and volatile organic compounds released by existing fiberboards during production lead to odor problems, affecting human health and product market competitiveness.
A preparation method for the melamine-modified urea-formaldehyde resin with a fragrance release micro-free formaldehyde content is adopted. Through the "alkali-acid-acid-base" synthesis process and the process route of adding urea and melamine in batches, the reaction temperature and pH value are controlled, the free formaldehyde content is reduced, and Chinese herbal powder is added to the resin to improve the aroma release and pharmacological effects.
It effectively reduces the formaldehyde emission of fiberboard, improves the odor level of the product, improves the curing speed and bonding strength of the resin, and enhances the antibacterial effect and health care performance of fiberboard.
Smart Images

Figure BDA0005209246160000071 
Figure BDA0005209246160000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives and relates to urea-formaldehyde resin, and in particular to a preparation method and application of a fragrance-releasing melamine-modified urea-formaldehyde resin with a low free formaldehyde content. Background Art
[0002] Fiberboard is a kind of board made of wood fiber or other plant fiber, which is prepared by fiber preparation, applied with synthetic resin, and pressed under heating and pressure. It is widely used in furniture industry and decoration due to its advantages of light weight, high strength, wide width, stable size, easy processing, and veneer. Wood has a natural odor, which comes from the volatile extracts contained in wood. When the wood chips are steamed, they are more likely to precipitate and produce an unpleasant odor. In addition, the unreacted free formaldehyde in the synthetic resin is released into the air, which will also produce a strong irritating odor. Therefore, the stimulating effect of fiberboard furniture or decorative materials on human olfaction has attracted more and more attention, especially the odor problem caused by formaldehyde and total volatile organic compounds (TVOC), which affects the human sensory effect and hypersensitivity effect, and even induces sick building syndrome such as headache, drowsiness, nausea, and runny nose.
[0003] In recent years, with the changes in domestic and international situations, the intensification of trade frictions, and the increasing uncertainty of world economic development, my country's fiberboard industry is facing an unfavorable situation of insufficient demand, overcapacity, insufficient operation, and corporate losses. In response to this situation, most fiberboard manufacturers actively develop various functional fiberboard products to enhance market competitiveness, especially in the fields of low formaldehyde, flame retardant, and waterproof. However, there is little research on increasing the beneficial volatile compounds of fiberboard, and even less attention is paid to the health care properties of fiberboard odor. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a method for preparing a fragrance-releasing melamine-modified urea-formaldehyde resin with a low free formaldehyde content.
[0005] In order to achieve the above objectives, the present invention is implemented according to the following technical solutions.
[0006] A method for preparing a fragrance-releasing melamine-modified urea-formaldehyde resin with a low free formaldehyde content comprises the following steps:
[0007] A. Add formaldehyde and water into the reactor, add diethanolamine and sodium hydroxide solution, and adjust the pH value of the reaction solution to 8.0-8.5;
[0008] B. Turn on the steam and raise the temperature to 58℃, add the first urea and the first melamine, at this time the temperature in the reactor will drop to about 50℃;
[0009] a) Automatically heat to 70°C, add resorcinol, the second urea and the second melamine, automatically heat to 75°C, add formic acid solution three times to adjust the pH value to 5.4-5.6, at this stage the molar ratio of formaldehyde to urea and melamine F / (U+1.5M) is 1.9-2.1;
[0010] b) Control the reaction temperature at 87-90°C and pH value at 5.4. During the acidic primary polycondensation reaction, continuously check the water solubility. When the reaction solution has white fog points in 45°C water, keep a sample to measure pH value and viscosity;
[0011] C. Immediately add the third urea, and 5 minutes later add the third melamine, and continue the acidic secondary polycondensation reaction. When the reaction solution has particles in 30°C water, it is the end point of the polycondensation reaction. Keep a sample to measure the pH value and viscosity. At this stage, the molar ratio of formaldehyde to urea and melamine F / (U+1.5M) is 1.1-1.3;
[0012] D. After reaching the end point of the second polycondensation reaction, the reaction was terminated with sodium hydroxide solution, the pH value was adjusted to 8.5, and the fourth urea was added, and the temperature was kept below 80°C for 10 minutes; then the fifth urea was added and the temperature was kept for 15 minutes;
[0013] E. After the heat preservation is completed, the temperature is lowered to 35-40°C, Chinese herbal medicine powder is added, the pH value is adjusted to 8.0-8.5, and the Chinese herbal medicine powder is stirred until it is evenly dispersed in the glue solution. Samples are taken to measure the pH value and viscosity, and the glue is discharged;
[0014] Among the various materials participating in the reaction, the mass of formaldehyde accounts for 41-43% of the total mass of the resin, the mass of melamine accounts for 4-6% of the total mass of the resin, the mass of diethanolamine accounts for 0.4-0.6% of the total mass of the resin, the mass of resorcinol accounts for 1-1.5% of the total mass of the resin, the mass of Chinese herbal medicine powder accounts for 10-15% of the total mass of the resin, and the balance is water. The molar ratio of formaldehyde to urea and melamine F / (U+1.5M) is 0.70-0.75.
[0015] In a preferred disclosed example of the present invention, the first urea in step B accounts for 27-31% of the total mass of urea; the first melamine accounts for 14-17% of the total mass of melamine; the second urea accounts for 4-8% of the total mass of urea; and the second melamine accounts for 48-52% of the total mass of melamine.
[0016] In a preferred disclosed example of the present invention, the third urea in step C accounts for 18-22% of the total mass of urea; the third melamine accounts for 33-36% of the total mass of melamine.
[0017] In a preferred disclosed example of the present invention, the fourth urea in step D accounts for 31-35% of the total mass of urea; the fifth urea accounts for 10-14% of the total mass of urea.
[0018] In a preferred disclosed example of the present invention, the Chinese herbal medicine powder in step E is composed of the following ingredients in mass percentage: 60-75wt% of Artemisia argyi, 10-15wt% of Patchouli, 10-15wt% of Chuanxiong, and 5-10wt% of Angelica dahurica.
[0019] Furthermore, the mass percentage of each component is: 60wt% of Artemisia argyi, 15wt% of Patchouli, 15wt% of Chuanxiong, and 10wt% of Angelica dahurica.
[0020] Furthermore, the average particle size of the Chinese herbal medicine powder ranges from 30 to 50 μm.
[0021] In the preferred disclosed examples of the present invention, the viscosity test adopts the Tu-4 cup test, the viscosity test temperature is 30°C, the viscosity endpoint test temperature is 25°C; the pH value test temperature is 35°C.
[0022] The melamine-modified urea-formaldehyde resin with low free formaldehyde content prepared by the method of the present invention has the following physical and chemical data: pH value is 8.0-8.5, viscosity is 16.0-20.0s, solid content is 55.0-58.0%, curing time is 200-300s, and free formaldehyde content is ≤0.08%.
[0023] The present invention does not adopt the traditional "base-acid-base" synthesis process, but the "base-acid-acid-base" preparation process. The entire resin synthesis process is divided into four stages: alkaline addition reaction, acidic primary polycondensation, acidic secondary polycondensation and alkaline post-treatment. Among them, formaldehyde is fed once, urea is fed five times, and melamine is fed three times.
[0024] Another object of the present invention is to apply the prepared aroma-releasing melamine-modified urea-formaldehyde resin with a low free formaldehyde content to the manufacture of health-preserving fiberboard.
[0025] Specifically, a manufacturing process of a health-care fiberboard includes: log peeling → chipping → wood chip screening → water washing → pre-cooking → cooking → hot grinding → gluing → drying → fiber sorting → paving → pre-pressing → hot pressing → board turning and cooling → conditioning and health care → sanding and sawing → inspection and grading → packaging and warehousing, wherein:
[0026] In the log peeling step, the log is selected from fir wood;
[0027] In the cooking step, the cooking temperature is controlled at 150-160°C and the cooking time shall not exceed 2 minutes;
[0028] In the sizing step, a fragrance-releasing melamine-modified urea-formaldehyde resin with a small free formaldehyde content is applied in the fiber ejection pipe, and the sizing amount is 200-280 kg / m 3 .
[0029] In the hot pressing step, the slab is hot pressed at a temperature of 160-240°C, and the pressure factor is 8.0-14.0s / mm. A continuous hot pressing process is adopted, and the hot pressing pressure distribution is as follows: the pressure in the inlet section rises to 2.0-3.6MPa, the pressure in the rebound section gradually decreases to 1.0-2.4MPa, the core layer insulation section gradually decreases to 0.05-0.4MPa, and the pressure in the thickness setting section is 1.0-1.4MPa.
[0030] Beneficial Effects
[0031] The present invention has the following advantages:
[0032] 1. Adopting the "base-acid-acid-base" synthesis process, based on the lower formaldehyde / (urea+melamine) molar ratio, the process route of "batch addition and multi-point segmentation" of urea and melamine, through step-by-step control, the polycondensation reaction is carried out at a higher reaction temperature and a lower pH, the degree of polycondensation is improved, the addition reactants are quickly converted into resins with large relative molecular mass, the content of hydroxymethyl, methylene ether, and hemiformal is reduced, and the reverse decomposition of methylene ether bonds and hydroxymethyl to produce free aldehydes is avoided, and the formation of "bulk" organic small molecules is promoted from the microscopic perspective, thereby increasing the curing speed of the resin. Adding the modifier diethanolamine in the alkaline addition reaction stage, it reacts with formaldehyde under weak alkaline conditions to form an imine structure, which can not only improve the bonding properties of the resin, reduce the free formaldehyde content, but also extend the storage period. In the first polycondensation reaction stage, melamine is used as a grafting bridge and resorcinol is introduced, which can effectively reduce the free formaldehyde content. At the same time, a cross-linked network structure is formed in the resin, which significantly improves the bonding strength of the resin.
[0033] 2. Add small-particle Chinese herbal powder to the resin, and after stirring, it will be evenly dispersed in the glue without precipitation. When applying the glue, the Chinese herbal powder is evenly sprayed on the fiber surface along with the adhesive to ensure the uniform and stable quality of the fiberboard. The Chinese herbal powder composed of wormwood, patchouli, Chuanxiong, and Angelica dahurica not only has the effect of releasing fragrance, but also has pharmacological effects such as antibacterial, antiviral, antiasthmatic, antitussive, expectorant, antiallergic, sedative, and immune. It has a certain effect on preventing influenza and epidemic diseases, and is beneficial to human health. In addition, the health-care fiberboard uses fir as the raw material. The fir alcohol contained in fir can kill bacteria in the air, inhibit human pathogens, and inhibit various skin inflammations. It also has the health-care effect of eliminating fatigue and relieving stress.
[0034] 3. The wood chips are softened by cooking at a lower temperature, shortening the cooking time and allowing more beneficial volatile compounds to be preserved in the wood chips. Based on the aroma-releasing melamine-modified urea-formaldehyde resin adhesive with a low free formaldehyde content and matching the appropriate hot pressing process, the health-care fiberboard produced has a reasonable density morphology distribution, high mechanical strength and good water resistance. The formaldehyde emission reaches the Japanese F★★★★ level, the odor level is 2, and the antibacterial rate against Escherichia coli and Staphylococcus aureus is greater than 99%, with significant antibacterial effects. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with the embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.
[0036] Example 1
[0037] 1. A method for preparing a fragrance-releasing melamine-modified urea-formaldehyde resin having a low free formaldehyde content, comprising:
[0038] The molar ratio F / (U+1.5M) of formaldehyde to urea and melamine is 0.72. The mass of formaldehyde accounts for 42% of the total mass of the resin, the mass of melamine accounts for 5% of the total mass of the resin, the mass of water accounts for 4% of the total mass of the resin, the mass of diethanolamine accounts for 0.5% of the total mass of the resin, the mass of resorcinol accounts for 1.5% of the total mass of the resin, and the Chinese herbal medicine powder accounts for 12% of the total mass of the resin (the mass percentage of each component is: 60% of Artemisia argyi, 15% of Patchouli sinensis, 15% of Chuanxiong, and 10% of Angelica dahurica; the average particle size of the Chinese herbal medicine powder is 30-40 μm). Among them: formaldehyde is added in 1 batch, urea is added in 5 batches, and melamine is added in 3 batches.
[0039] The preparation process is as follows:
[0040] A. Add formaldehyde and water into the reactor, add diethanolamine and sodium hydroxide solution, and adjust the pH value of the reaction solution to 8.0-8.5;
[0041] B. Turn on the steam and raise the temperature to 58°C, add the first urea and the first melamine (the first urea accounts for 28% of the total mass of urea; the first melamine accounts for 15% of the total mass of melamine). At this time, the temperature in the reactor will drop to about 50°C. Generally, do not heat it up.
[0042] a) Automatically heat to 70°C, add resorcinol, second urea and second melamine (second urea accounts for 6% of the total mass of urea; second melamine accounts for 50% of the total mass of melamine), automatically heat to 75°C, add formic acid solution three times to adjust the pH value to 5.4-5.6, at this stage the molar ratio of formaldehyde to urea and melamine F / (U+1.5M) is 2.0,
[0043] b) Control the maximum reaction temperature at about 88°C, pH = 5.4, and not exceed 90°C;
[0044] During the acidic primary polycondensation reaction, the water solubility was constantly checked. When the reaction solution showed white fog points in 45°C water, samples were retained to measure pH and viscosity.
[0045] C. Immediately add the third urea, and 5 minutes later add the third melamine (the third urea accounts for 19% of the total mass of urea; the third melamine accounts for 35% of the total mass of melamine), and continue the acidic secondary polycondensation reaction. When the reaction liquid has particles in 30℃ water, it is the end point of the polycondensation reaction, and keep the sample to measure the pH value and viscosity; at this stage, the molar ratio of formaldehyde to urea and melamine F / (U+1.5M) is 1.3;
[0046] D. After reaching the end point of the second polycondensation reaction, the reaction was terminated with sodium hydroxide solution, the pH value was adjusted to 8.5, and the fourth urea was added (the fourth urea accounted for 36% of the total mass of urea) at 80°C.
[0047] Keep warm for 10 minutes; then add the fifth urea (the fifth urea accounts for 11% of the total urea mass) and keep warm for 15 minutes;
[0048] E. After the insulation is completed, cool down to 35-40℃, add Chinese herbal powder, adjust the pH value to 8.0-8.5, stir for 20 minutes, wait for the Chinese herbal powder to be evenly dispersed in the glue, take samples to measure the pH value and viscosity, and then produce glue.
[0049] The obtained aroma-releasing melamine-modified urea-formaldehyde resin has the following physical and chemical data: pH value is 8.3, viscosity is 17.50s, solid content is 56.1%, curing time is 255s, and free formaldehyde content is 0.05%.
[0050] 2. Manufacturing process of 7.6mmF★★★★ grade health-care fiberboard
[0051] A manufacturing process of a 7.6mmF★★★★ grade health-care fiberboard, comprising the following steps: log peeling → chipping → wood chip screening → water washing → pre-cooking → cooking → hot grinding → gluing → drying → fiber sorting → paving → pre-pressing → hot pressing → board turning and cooling → conditioning and health care → sanding and sawing → inspection and grading → packaging and warehousing, wherein:
[0052] Fir is selected as the raw material. After the logs are peeled, they are made into wood chips by a disc chipper. After screening, qualified wood chips with a length and width of 10 to 40 mm and a thickness of 2 to 8 mm are obtained. They are then washed with water to remove impurities such as mud, stone, and metal to ensure the cleanliness of the wood chips.
[0053] The qualified wood chips are preheated in a pre-cooking cylinder at a temperature of 95±5°C. The wood chips are softened by cooking at a pressure of 8.5 to 8.8 bar, a temperature of 150 to 160°C, and a cooking time of 1.5 minutes.
[0054] The wood chips enter the hot mill through the belt screw, and molten paraffin is added to the mill. The amount of paraffin added is about 8kg / m 3 , fiber separation output 20 ~ 22 tons / hour.
[0055] The fragrance-releasing melamine-modified urea-formaldehyde resin adhesive and curing agent prepared in this embodiment are applied to the fiber ejection pipe, and the amount of adhesive applied is 220 kg / m 3 ; The curing agent is ammonium sulfate, and the added amount is 2.5% of the absolute dry resin mass.
[0056] During the drying process, the moisture content of the fiber is controlled at 9.0-10.0%.
[0057] Adjust the paving density to ensure the slab density is 780-790kg / m 3 .
[0058] The slab was hot pressed at 170-230℃, with a pressure factor of 8.0-8.4s / mm. A continuous hot pressing process was used, and the hot pressing temperature and hot pressing pressure were set as follows: five temperature zones were used: 225±5℃, 223±5℃, 205±5℃, 183±5℃, and 165±5℃. Hot pressing pressure distribution: the pressure in the inlet section increased to 2.2-3.2MPa, the pressure in the rebound section gradually decreased to 1.2-1.8MPa, the core layer insulation section gradually decreased to 0.15-0.25MPa, and the pressure in the thickness setting section was 1.0-1.3MPa.
[0059] The plates coming out of the press are cooled by turning over, stacked and cured for 48 hours before sanding. The four sanding processes are distributed as follows: the first sanding accounts for 55-60% (50 mesh sanding belt), the second sanding accounts for 20-25% (80 mesh sanding belt), the third sanding accounts for 10-15% (120 mesh sanding belt), and the fourth sanding accounts for 5-10% (180 mesh sanding belt).
[0060] After sanding, the substrate is sawn, inspected and graded, and then packaged and put into storage.
[0061] The 7.6mmF★★★★ grade health-care fiberboard obtained through the above steps was tested according to the standard requirements of GB / T 11718-2021 "Medium Density Fiberboard" for furniture-type medium density fiberboard (MDF-FN REG) used in a dry state. The results are as follows:
[0062]
[0063] Example 2
[0064] 1. A method for preparing a fragrance-releasing melamine-modified urea-formaldehyde resin having a low free formaldehyde content, comprising:
[0065] The molar ratio F / (U+1.5M) of formaldehyde to urea and melamine is 0.75. The mass of formaldehyde accounts for 43% of the total mass of the resin, the mass of melamine accounts for 6% of the total mass of the resin, the mass of water accounts for 4% of the total mass of the resin, the mass of diethanolamine accounts for 0.5% of the total mass of the resin, the mass of resorcinol accounts for 1.3% of the total mass of the resin, and the Chinese herbal medicine powder accounts for 15% of the total mass of the resin (the mass percentage of each component is: 60% of Artemisia argyi, 15% of Patchouli sinensis, 15% of Chuanxiong, 10% of Angelica dahurica, and the average particle size of the Chinese herbal medicine powder is 30-40 microns). Among them: formaldehyde is added in 1 batch, urea is added in 5 batches, and melamine is added in 3 batches.
[0066] The preparation process is as follows:
[0067] A. Add formaldehyde and water into the reactor, add diethanolamine and sodium hydroxide solution, and adjust the pH value of the reaction solution to 8.0-8.5;
[0068] B. Turn on the steam and raise the temperature to 58°C, add the first urea and the first melamine (the first urea accounts for 29% of the total mass of urea; the first melamine accounts for 15% of the total mass of melamine). At this time, the temperature in the reactor will drop to about 50°C, and generally do not heat up;
[0069] a) Automatically heat to 70°C, add resorcinol, second urea and second melamine (second urea accounts for 6% of the total mass of urea; second melamine accounts for 50% of the total mass of melamine), automatically heat to 75°C, add formic acid solution three times to adjust the pH value to 5.4-5.6, at this stage the molar ratio of formaldehyde to urea and melamine F / (U+1.5M) is 2.0,
[0070] b) Control the maximum reaction temperature at about 88°C, pH = 5.4, and not exceed 90°C,
[0071] During the acidic primary polycondensation reaction, the water solubility was constantly checked. When the reaction solution showed white fog points in 45°C water, samples were retained to measure pH and viscosity.
[0072] C. Immediately add the third urea, and 5 minutes later add the third melamine (the third urea accounts for 20% of the total mass of urea; the third melamine accounts for 35% of the total mass of melamine), and continue the acidic secondary polycondensation reaction. When the reaction liquid has particles in 30℃ water, it is the end point of the polycondensation reaction. Keep a sample to measure the pH value and viscosity. At this stage, the molar ratio of formaldehyde to urea and melamine F / (U+1.5M) is 1.3;
[0073] D. After reaching the end point of the second polycondensation reaction, terminate the reaction with sodium hydroxide solution and adjust the pH value to 8.5
[0074] Then, the fourth urea was added (the fourth urea accounted for 33% of the total urea mass ratio) at 80°C.
[0075] Keep warm for 10 minutes; then add the fifth urea (the fifth urea accounts for 12% of the total urea mass) and keep warm for 15 minutes;
[0076] E. After the heat preservation is completed, cool down to 35-40℃, add Chinese herbal medicine powder, adjust the pH value to 8.0-8.5, and stir.
[0077] Stir for 20 minutes until the Chinese herbal powder is evenly dispersed in the glue, take samples to measure the pH value and viscosity, and then produce glue.
[0078] The physical and chemical data of the prepared aroma-releasing melamine-modified urea-formaldehyde resin with a low free formaldehyde content are as follows: pH value is 8.2, viscosity is 18.60s, solid content is 57.4%, curing time is 223s, and free formaldehyde content is 0.07%.
[0079] 2. 18mmF★★★★ grade health-care fiberboard manufacturing process
[0080] A manufacturing process of 18mmF★★★★ grade health-care fiberboard, comprising the following steps: log peeling → chipping → wood chip screening → water washing → pre-cooking → cooking → hot grinding → gluing → drying → fiber sorting → paving → pre-pressing → hot pressing → board turning and cooling → conditioning and health care → sanding and sawing → inspection and grading → packaging and warehousing, wherein:
[0081] The wood is made of fir as raw material. After the logs are peeled, they are made into wood chips by a disc chipper. After screening, qualified wood chips with a length and width of 10-40 mm and a thickness of 2-8 mm are obtained. Then they are washed with water to remove impurities such as sand, stones, and metals to ensure the cleanliness of the wood chips.
[0082] Qualified wood chips are preheated in a pre-cooking tank at 95±5℃. The wood chips are softened by cooking at a pressure of 8.0-8.3 bar, a temperature of 150-160℃, and a cooking time of 1.8 minutes.
[0083] The wood chips enter the hot mill through the belt screw, and molten paraffin is added to the mill. The amount of paraffin added is about 5kg / m 3 , fiber separation output 16-18 tons / hour;
[0084] The fragrance-releasing melamine-modified urea-formaldehyde resin adhesive and curing agent prepared in this embodiment are applied to the fiber ejection pipe, and the amount of adhesive applied is 250 kg / m 3; The curing agent is ammonium sulfate, and the addition amount is 2.5% of the absolute dry resin mass;
[0085] During the drying process, the moisture content of the fiber is controlled at 7.0-8.0%;
[0086] Adjust the paving density to ensure the slab density is 760-770kg / m 3 ;
[0087] The slab is hot pressed at 180-240℃, with a pressure factor of 10.5-11.5s / mm. A continuous hot pressing process is used, and the hot pressing temperature and hot pressing pressure are set as follows: five temperature zones are used: 235±5℃, 233±5℃, 220±5℃, 200±5℃, 185±5℃. Hot pressing pressure distribution: the pressure in the inlet section rises to 2.0-2.8MPa, the pressure in the rebound section gradually decreases to 0.8-1.2MPa, the core layer insulation section gradually decreases to 0.05-0.08MPa, and the pressure in the thickness setting section is 1.0-1.4MPa.
[0088] The plates coming out of the press are cooled by turning over, stacked and cured for 48 hours before sanding. The four sanding processes are distributed as follows: the first sanding accounts for 55-60% (50 mesh sanding belt), the second sanding accounts for 20-25% (80 mesh sanding belt), the third sanding accounts for 10-15% (120 mesh sanding belt), and the fourth sanding accounts for 5-10% (180 mesh sanding belt).
[0089] After sanding, the substrate is sawn, inspected and graded, and then packaged and put into storage.
[0090] The 18mmF★★★★ grade health-care fiberboard obtained through the above steps was tested according to the standard requirements of GB / T 11718-2021 "Medium Density Fiberboard" for furniture-type medium density fiberboard (MDF-FN REG) used in a dry state. The results are as follows:
[0091]
[0092] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a fragrance-releasing melamine-modified urea-formaldehyde resin with a low free formaldehyde content, characterized in that: The steps include: A. Place formaldehyde and water into the reactor, add diethanolamine and sodium hydroxide solution, and adjust the pH value of the reaction solution to 8.0-8.5; B. Turn on the steam and raise the temperature to 58℃, add the first urea and the first melamine, at this time the temperature in the reactor will drop to about 50℃; a) Automatically heat to 70°C, add resorcinol, the second urea and the second melamine, automatically heat to 75°C, add formic acid solution three times to adjust the pH value to 5.4-5.6, at this stage the molar ratio of formaldehyde to urea and melamine F / (U+1.5M) is 1.9-2.1; b) Control the reaction temperature at 87-90°C and pH value at 5.
4. During the acidic primary polycondensation reaction, continuously check the water solubility. When the reaction solution has white fog points in 45°C water, keep a sample to measure pH value and viscosity. C. Immediately add the third urea, and 5 minutes later add the third melamine, and continue the acidic secondary polycondensation reaction. When the reaction liquid has particles in 30℃ water, it is the end point of the polycondensation reaction. Keep a sample to measure the pH value and viscosity. At this stage, the molar ratio of formaldehyde to urea and melamine F / (U+1.5M) is 1.1-1.3; D. After reaching the end point of the second polycondensation reaction, terminate the reaction with sodium hydroxide solution, adjust the pH value to 8.5, add the fourth urea, and keep it warm at 80℃ for 10 minutes; then add the fifth urea and keep it warm for 15 minutes; E. After the heat preservation is completed, cool down to 35-40℃, add Chinese herbal medicine powder, adjust the pH value to 8.0-8.5, stir until the Chinese herbal medicine powder is evenly dispersed in the glue, take samples to measure the pH value and viscosity, and then discharge the glue; Among the various materials participating in the reaction, the mass of formaldehyde accounts for 41-43% of the total mass of the resin, the mass of melamine accounts for 4-6% of the total mass of the resin, the mass of diethanolamine accounts for 0.4-0.6% of the total mass of the resin, the mass of resorcinol accounts for 1-1.5% of the total mass of the resin, the mass of Chinese herbal medicine powder accounts for 10-15% of the total mass of the resin, and the balance is water. The molar ratio of formaldehyde to urea and melamine F / (U+1.5M) is 0.70-0.
75.
2. The method for preparing the aroma-releasing melamine-modified urea-formaldehyde resin with a low free formaldehyde content according to claim 1, characterized in that: In step B, the first urea accounts for 27-31% of the total mass of urea; the first melamine accounts for 14-17% of the total mass of melamine; the second urea accounts for 4-8% of the total mass of urea; and the second melamine accounts for 48-52% of the total mass of melamine.
3. The method for preparing the aroma-releasing melamine-modified urea-formaldehyde resin with a low free formaldehyde content according to claim 1, characterized in that: The third urea in step C accounts for 18-22% of the total mass of urea; the third melamine accounts for 33-36% of the total mass of melamine.
4. The method for preparing the aroma-releasing melamine-modified urea-formaldehyde resin with a low free formaldehyde content according to claim 1, characterized in that: The fourth urea in step D accounts for 31-35% of the total mass of urea; the fifth urea accounts for 10-14% of the total mass of urea.
5. The method for preparing the aroma-releasing melamine-modified urea-formaldehyde resin with low free formaldehyde content according to claim 1, characterized in that: The Chinese herbal medicine powder in step E is composed of the following components in terms of mass percentage: 60-75wt% of Artemisia argyi, 10-15wt% of Patchouli, 10-15wt% of Chuanxiong, and 5-10wt% of Angelica dahurica.
6. The method for preparing the aroma-releasing melamine-modified urea-formaldehyde resin with little free formaldehyde content according to claim 1, characterized in that: The Chinese herbal medicine powder in step E is composed of the following components in terms of mass percentage: 60wt% of Artemisia argyi, 15wt% of Patchouli, 15wt% of Ligusticum chuanxiong, and 10wt% of Angelica dahurica.
7. The method for preparing the aroma-releasing melamine-modified urea-formaldehyde resin with little free formaldehyde content according to claim 1, characterized in that: The average particle size of the Chinese herbal medicine powder in step E is in the range of 30 to 50 μm.
8. The method for preparing the aroma-releasing melamine-modified urea-formaldehyde resin with little free formaldehyde content according to claim 1, characterized in that: The viscosity test was conducted using a Tu-4 cup test. The test temperature was 30°C, the viscosity endpoint test temperature was 25°C, and the pH value test temperature was 35°C.
9. The aroma-releasing melamine-modified urea-formaldehyde resin with little free formaldehyde content prepared according to any one of claims 1 to 8, characterized in that: The physical and chemical data are pH value of 8.0-8.5, viscosity of 16.0-20.0s, solid content of 55.0-58.0%, curing time of 200-300s, and free formaldehyde content of ≤0.08%.
10. A manufacturing process of a health-preserving fiberboard, comprising: Log peeling → chipping → wood chip screening → water washing → pre-cooking → cooking → hot grinding → gluing → drying → fiber sorting → laying → pre-pressing → hot pressing → flap cooling → conditioning and curing → sanding and sawing → inspection and grading → packaging and warehousing, including: In the log peeling step, the log is selected from fir wood; In the cooking step, the cooking temperature is controlled at 150-160°C and the cooking time shall not exceed 2 minutes; In the sizing step, the fragrance-releasing melamine-modified urea-formaldehyde resin with a small free formaldehyde content as claimed in claim 9 is applied in the fiber ejection pipe, and the sizing amount is 200-280 kg / m 3 ; In the hot pressing step, the slab is hot pressed at a temperature of 160-240°C, and the pressure factor is 8.0-14.0s / mm. A continuous hot pressing process is adopted, and the hot pressing pressure distribution is as follows: the pressure in the inlet section rises to 2.0-3.6MPa, the pressure in the rebound section gradually decreases to 1.0-2.4MPa, the core layer insulation section gradually decreases to 0.05-0.4MPa, and the pressure in the thickness setting section is 1.0-1.4MPa.
Citation Information
Cited By
Urea formaldehyde stable slow-release fertilizer and preparation method thereof
CN122427044A